Telepathic Emissions: Edwin J. Houston on “Cerebral Radiation” - Alvarado, Carlos S. (Journal of Scientific Exploration, 2015)
Interest in telepathy during the nineteenth-century developed in the context of ideas of magnetic, nervous and psychic forces said to project from the physical body to cause various phenomena, as seen in the literatures of mesmerism, Spiritualism, and psychical research. An article about cerebral radiations authored by American electrical engineer Edwin J. Houston in 1892 is reprinted and commented. Houston speculated that cerebral waves were projected to other brains via the ether, a process involving resonance with a similarly disposed brain. These ideas were affected by concepts from physics dealing with such forces as magnetism and constructs like the ether. In fact, the phenomena of thought-transference stimulated many speculations involving ideas of brain waves and radiations that were part of a tendency to reduce unexplained phenomena to physical and physiological principles, or in this case, biophysical ones. Houston's paper is one of the most detailed ideas of this sort published in the nineteenth-century. Nonetheless, Houston showed no familiarity with the literature about telepathy of his times. While his article did not originate ideas of this sort, it is a good representative of speculations of the period about what today we refer as physical transmission models of ESP. Keywords: Edwin J. Houston; Telepathy; thought-transference; history of telepathy; brain waves; cerebral radiations.